The online communication of the Spanish film production companies. : Product promotion - García Mirón, Silvia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The audiovisual sector is a key strategic sector for the economic and cultural development of a country and a determining factor in the foreign promotion of the country brand (cf. Tribaldos Macía, 2013). With this purpose, in 2021 the Government of Spain presented the Spain Audiovisual Hub and in 2023 a series of measures were launched to boost the internationalization of the sector. In this context, this research is presented focused on analyzing the digital presence of the main Spanish film production companies with the aim of observing their communication strategies to promote their products and, therefore, the Spanish audiovisual sector.